Position-space gluon propagator from quenched lattice QCD - de Soto Feliciano (EPJ Web of Conferences, 2022)
We report novel lattice QCD results for the position-space gluon propagator in Landau gauge from quenched simulations. Using standard Wilson action, we computed gluon propagator in position space with a detailed treatment of hypercubic errors. Gluon propagator is scrutinized in position-space, discussing on the usefulness of the long-distance behavior of gluon propagator for constraining the gluon spectral function or the deep infrared running of the gluon propagator in momentum-space.